Robin Hood (1973) [videorecording (DVD)] - Reitherman, Wolfgang, 1909-1985; Bedford, Brian, 1935-2016; Miller, Roger, 1936-1992; Harris, Phil, 1904-1995 (Disney DVD., 2013)
Join Robin Hood, his trusted companion Little John, and his hilarious band of Merry Men as they outfox greedy Prince John to save the good people of Nottingham. Dashing from one daring deed to the next, Robin won't rest until he wins the hand of Maid Marian and restores King Richard to the throne.